Given parameters:
Quadratic expression:
x² - 6x + 7 = 0
Solve using quadratic formula;
x = ![\frac{-b +/- \sqrt{b^{2 } - 4ac} }{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%20%2B%2F-%20%5Csqrt%7Bb%5E%7B2%20%7D%20-%204ac%7D%20%7D%7B2a%7D)
From the equation;
a = 1, b = -6 and c = 7
Input the parameters and solve;
x = ![\frac{-(-6) +/- \sqrt{-6^{2 } + 4 x 1 x 7 } }{2 x 1}](https://tex.z-dn.net/?f=%5Cfrac%7B-%28-6%29%20%2B%2F-%20%5Csqrt%7B-6%5E%7B2%20%7D%20%2B%204%20x%201%20x%207%20%7D%20%7D%7B2%20x%201%7D)
x = ![\frac{6 +/- \sqrt{36} +28 }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B6%20%2B%2F-%20%5Csqrt%7B36%7D%20%2B28%20%7D%7B2%7D)
x = ![\frac{6 +/- \sqrt{64} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B6%20%2B%2F-%20%5Csqrt%7B64%7D%20%7D%7B2%7D)
x =
or ![\frac{6-8}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B6-8%7D%7B2%7D)
x = 7 or -1
Answer:
False
Step-by-step explanation:
The analysis of variance may be described as an hypothesis test which is used to make comparison between variables of two or more independent groups. The null hypothesis is always of the notion that there is no difference in the means. While the alternative hypothesis is the opposite, for two independent groups, the alternative hypothesis is that both means are different, or not equal or not the same. However. When we have more than 2 independent groups, then the alternative hypothesis is stated as : 'the means are not all equal'. This means that the means of each group does not all have to be different, but the mean of one group may be different from that of the other groups or the mean of two groups are different from the other groups and so on.
Distribute the 5 to each of the numbers so you should get 5x+5+5x+5+5x+35. after this you should combine like terms, all of the 5’s & the 35 and 5x’s. you should have 15x+45. then you divide 45 by the 15 and you should get x=3
Answer:
Step-by-step explanation:
The graph of f(x) = x is a straight line passing through the origin with slope of m = 1. The graph of f(x - 1) is obtained by translating the entire graph of f(x) 1 unit to the right.
The current area is 15 x 9 = 135 square feet.
He wants to increase both the length and width by X:
Set up an equation:
(15 +x) * (9 +x) = 135 * 2
Simplify :
x^2 + 24x + 135 = 270
Subtract 270 from both sides:
x^2 + 24x - 135 = 0
Use the quadratic formula to solve for x:
-24 +/- √(24^2 - 4(1*-135) / 2*1
x = 4.7 or -28.7
The answer has to be a positive value, so x = 4.7 feet.